Work environment, career development, and workload: determinants of job satisfaction in the civil service police unit of barito kuala regency - Devi, Made Saraswati; Nastiti, Rizky; Bachtiar, Yanuar; Daud, Ibrahim (Institute of Computer Science (IOCS), 2025)
Employee job satisfaction is a critical factor influencing organizational performance and effectiveness, particularly in public sector institutions such as the Civil Service Police Unit. A positive work environment and career development opportunities are known to enhance employee engagement, motivation, and productivity, while workload has been identified as a potential stressor that can undermine job satisfaction. This study investigates the effects of the work environment, career development, and workload on the job satisfaction of employees at the Civil Service Police Unit in Barito Kuala Regency. The study involved a sample of 45 employees, and data were analyzed to assess the relationships between these variables. The findings reveal that both the work environment and career development have a positive and significant impact on job satisfaction. In contrast, workload does not have a significant effect on job satisfaction. These results suggest that fostering a supportive and well-structured work environment, along with offering opportunities for career development, can significantly enhance employee satisfaction and contribute to organizational success. Meanwhile, workload management alone may not be a key determinant of job satisfaction in this context, highlighting the need for a more holistic approach to employee well-being. These insights can inform human resource policies and management strategies aimed at improving job satisfaction and optimizing employee performance in public service agencies